1981
DOI: 10.1111/j.1943-278x.1981.tb00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Common Characteristics of Latency‐Age Suicidal Children: A Tentative Model Based on Case Study Analyses

Abstract: Eleven latency-age (6 1/2 to 12 1/2) boys and girls who attempted or threatened suicide were investigated by means of the following information: intensive interviews, therapeutic meetings, direct observation in school, meetings with teachers, and survey of school records. The families of the children were also interviewed. In spite of the many differences between the children's personalities and backgrounds, some common dynamic features seemed to emerge: (a) There was a suicidal parent in the family, in most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…According to Orbach and colleagues (1981), AD and R D are key factors in suicidal behavior. Although they may appear to overlap, these dimensions are theoretically different and measurably distinct (Orbach, Gross, & Glaubman, 1981). Suicidal children have low AL, high R L , high AD, and low RD.…”
Section: University Of Southern Mississippimentioning
confidence: 97%
See 2 more Smart Citations
“…According to Orbach and colleagues (1981), AD and R D are key factors in suicidal behavior. Although they may appear to overlap, these dimensions are theoretically different and measurably distinct (Orbach, Gross, & Glaubman, 1981). Suicidal children have low AL, high R L , high AD, and low RD.…”
Section: University Of Southern Mississippimentioning
confidence: 97%
“…To replicate and expand the Orbach, Gross, and Glaubman (1981) model of suicidal behauior in children, 60 children, aces 6 to 13, reported their own suicidal thoughts and behaviors using the Suicidal Behauiors Questionnaire (Linehan, 1981 In response to the growing concern about youth suicide, Orbach, Gross, and Glaubman (1981) have proposed a model of children's suicidal behavior having four dimensions: attractiveness and repulsiveness of life and attractiveness and repulsiveness of death. Each has motivational, cognitive, and emotional components.…”
Section: University Of Southern Mississippimentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that suicidal children are more likely than others to be victims of child abuse and neglect (22,38,39,(54)(55)(56). In addition, parental conflict, unclear role definitions, and inflexible structure often characterize the families of suicidal children (47,57,58). Several studies and clinical observations show that suicidal children have many negative experiences at school as well as at home.…”
Section: Testing the Model: Developmental Differences In The Suicide mentioning
confidence: 98%
“…Considerations of suicide require a means to overcome the fear of annihilation; a belief in the reversibility of death provides the means for some children, in spite of their comprehension of the irreversibility of impersonal death. Orbach et al ( 1978Orbach et al ( , 1979aOrbach et al ( , 1979bOrbach et al ( , 1981Orbach et al ( , 1983Orbach et al ( , 1984 consider suicidal children's belief in the reversibility of death to constitute part of a defensive process which allows suicidal action to occur. The defensive process involves a cognitive distortion in the comprehension of the finality of personal death.…”
Section: )mentioning
confidence: 99%